Application of Molecularly Imprinted Polymers for the - Garcia, Raquel (2011)
The increasing application of pesticides for agricultural purposes involves serious risk to the environment and human health due to either exposure or through residues in food and drinking water. Since food safety is of mandatory importance there is a growing interest on the development of selective, simple, rapid, cost-effective and reliable analytical methodologies in order to ensure that pesticides residues should not be found at levels above the established maximum pesticide residue limits (MRLs). In recent years, a new methodology based on the development of molecularly imprinting polymers (MIPs) allows not only pre-concentration and cleaning of the sample but also selective extraction of the target analyte, which is crucial, particularly when the sample is complex and impurities can interfere with quantification. The scope of this review is to provide a general overview on MIPs field, with emphasis on MIP preparation and its use as sorbents for solid-phase extraction. This paper will be focused on the review of the current state of the art in the use of MIPs as selective materials in molecularly imprinted solid-phase extraction (MISPE) for the analysis of pesticide residues from food matrices. A review of preparation and application of MIPs in food matrices, will also be discussed.